Effects of structured contraceptive counseling in young women: Secondary analyses of a cluster randomized controlled trial (the LOWE trial) - Karin Emtell Iwarsson; Volodymyr Podolskyi; Isabella Bizjak; Helena Kopp Kallner; Kristina Gemzell‐Danielsson; Niklas Envall (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Unwanted pregnancy constitutes a huge health issue. Long‐acting reversible contraception (LARC) are the most effective methods for preventing unwanted pregnancy, especially among young women. This study evaluates the intervention effect of structured contraceptive counseling on the choice, initiation, and use of LARC in young women. Material and Methods This is a secondary analysis of women aged 18–25, enrolled in a multicenter cluster randomized controlled trial performed in abortion, youth, and maternal health clinics across the Stockholm County in Sweden. Clinics were randomized (1:1) to provide structured contraceptive counseling (intervention) or standard counseling (control). Surveys were administered at the clinic visit and follow‐ups at 3, 6, and 12 months. Primary outcome focused on the choice of LARC among women 18–25 years of age. Secondary outcomes included initiation, and use of LARC at 3 and 12 months, satisfaction with the counseling received and information on extended use of combined hormonal contraceptives. The study was registered at Clinicaltrials.gov (NCT03269357). Results From September 2017 to May 2019, 770 women aged 18–25 years from 28 clinics/clusters were recruited. There was a significant intervention effect on LARC choice (aOR 5.96, 95% CI 3.25–10.94), initiation (aOR 4.43, 95% CI 2.32–8.46), and use at 12 months (aOR 2.21, 95% CI 1.31–3.73). The odds of LARC choice at pre‐booked visits were higher and more women received information about extended‐use regimen for short‐acting reversible contraception in the intervention group compared to the control group. The intervention package was well received, but with higher satisfaction at pre‐booked compared to drop‐in visits. Conclusions Our study demonstrates that comprehensive structured contraceptive counseling significantly increases LARC choice, initiation and use, with high satisfaction among young participants, especially at pre‐booked visits. The results highlight an approach that merits implementation to increase quality of care in contraceptive services, to enhance reproductive health for adolescents and young adults.